2011
DOI: 10.1007/s11085-011-9246-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen and Water Vapour on the Kinetics of Chromium Oxide Growth at High Temperature

Abstract: International audienceIn support of the selection of structural materials for heat exchangers in helium-cooled high temperature reactors, the oxidation behaviour of the Ni-base chromia-former alloy 230 was investigated at 850 A degrees C in diluted helium atmosphere with a low water vapour content. In such a media, the equivalent partial pressure of oxygen (imposed by the 850 degrees C in diluted helium atmosphere with a low water vapour content. In such a media, the equivalent partial pressure of oxygen (impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Based on the XRD pattern and the Raman spectra, the Cr-O scale mainly composes of Cr 2 O 3 . Guillou et al [ 38 ] also found the thin external Cr-O scale is denser without any pores. Hansel et al [ 39 ] proved that local surface catalysis of H 2 O dissociation at low P O2 values causes local acceleration in the oxidation rate and the growth of protruding oxide whiskers.…”
Section: Resultsmentioning
confidence: 98%
“…Based on the XRD pattern and the Raman spectra, the Cr-O scale mainly composes of Cr 2 O 3 . Guillou et al [ 38 ] also found the thin external Cr-O scale is denser without any pores. Hansel et al [ 39 ] proved that local surface catalysis of H 2 O dissociation at low P O2 values causes local acceleration in the oxidation rate and the growth of protruding oxide whiskers.…”
Section: Resultsmentioning
confidence: 98%
“…For alloy Inconel 600 and alloy Incoloy 825 with relatively lower chromium content, therefore, the breakaway corrosion was more prone to happen after a shorter time. In addition, with the same exposure temperatures and oxygen partial pressures, the defect density of oxides formed in SCW is higher than that in steam environment [54,55]. The concentrated defects of ''protective'' oxides accelerated the ingress of sulfur, further resulting in the loss of oxides' protective immune function in advance.…”
Section: Discussionmentioning
confidence: 96%
“…This was done to describe the effect of the gas composition on the chromia growth rate as well as on the electrical conductivity of chromia-based scales. 30 The apparent contradictions in results from various literature sources may partly be related to the fact that in several of the mentioned studies commercially available alloy systems were used; the results may, thus, be affected by commonly present impurities and/or minor alloying additions such as titanium and manganese. 31 A major problem in interpreting the results on the basis of point defects is that chromia growth is claimed to be dominated by grain boundary rather than lattice transport.…”
Section: Single Stage Exposuresmentioning
confidence: 98%